2018
DOI: 10.1109/tps.2018.2873947
|View full text |Cite
|
Sign up to set email alerts
|

The Electrothermal Instability on Pulsed Power Ablations of Thin Foils

Abstract: email to discuss past research and ideas for new experiments. Particular thanks go to Dr. Jacob Zier, a former graduate student in our lab who attempted the daunting task of teaching me how to run the LTD in only six months as he wrote his own dissertation. Thanks also go to Dr. Matthew Gomez, whom I also briefly overlapped with as a graduate student and who has provided advice on numerous occasions. Mark Perrault provided indispensable support to my research as our lab electrician, machinist, and safety offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Recent work has suggested that the higher-than-expected azimuthal correlation could be related to key missing physics in the seeding of the MRT instability. Presently, it is proposed that the early time electrothermal instability (ETI) [65][66][67][68][69][70][71][72][73][74][75] could explain the azimuthal correlation, even with axiallyfinished targets. This instability arises due to localized current enhancement in materials where the resistivity increases with temperature and/or decreases with density.…”
Section: Instability Developmentmentioning
confidence: 99%
“…Recent work has suggested that the higher-than-expected azimuthal correlation could be related to key missing physics in the seeding of the MRT instability. Presently, it is proposed that the early time electrothermal instability (ETI) [65][66][67][68][69][70][71][72][73][74][75] could explain the azimuthal correlation, even with axiallyfinished targets. This instability arises due to localized current enhancement in materials where the resistivity increases with temperature and/or decreases with density.…”
Section: Instability Developmentmentioning
confidence: 99%
“…The experimental facility assembled at UM to test the Laser Gate concept included a small current pulser, 17,18 an iPhone 6s video camera, and a 12-frame brightfield laser schlieren/shadowgraphy imaging system (see Fig. 5).…”
Section: Experimental Test Facilitymentioning
confidence: 99%
“…In the past a number of publications reported that loads made of flat or cylindrical foils, composed of different materials and different sizes, were exploded with pulse high-current generators for the purpose of various applications [1][2][3][4][5][6][7][8][9][10][11][12]. Under the 1000 Å), as well as soft x-ray (SXR) radiation (2 Å < λ < 100 Å) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%